The Mediating Effect of Distributive Justice in the Relationship Between Pay Design and Job Satisfaction - Azman, Ismail; Dayang Kartini, Abang Ibrahim; Antonia, Girardi (University of Arad, 2009)
This study was conducted to measure the mediating effect of distributive justice in the relationship between pay design issues and job satisfaction. A survey method was used to gather 190 usable questionnaires from academic employees who have worked in Malaysian public community college (PUBLICOLLEGE).Outcomes from step wise regression analysis showed that relationship between pay design features significantly correlated with job satisfaction. This result confirms that distributive justice plays an important role as a mediating variable in the pay design models of the organisational sector sample. In addition, implications of this study to compensation theory and practice, conceptual and methodological limitations, as well as directions for future research are discussed.